Metabolism of Pyrimidine Nucleotides in a Microorganism: III. Enzymatic Production of Ribose-5-Phosphate from Uridine-5′-Monophosphate by Pseudomonas oleovorans - Sakai, Takuo (1971)
A study was made to develop a new method for the production of ribose-5-phosphate (R-5-P) from uridine-5′-monophosphate (UMP) by the action of nucleotide-N-ribosidase of Pseudomonas oleovorans, and a suitable medium for the formation of nucleotide-N-ribosidase was established. For the enzymatic conversion of UMP to R-5-P, a cell suspension was employed as the enzyme source. Although degradation of R-5-P, the desired product, occurred during the course of the enzyme reaction, it was prevented by the addition of an appropriate amount of zinc ion and resulted in a stoichiometric conversion of UMP to R-5-P and uracil. Accumulated R-5-P was readily isolated by ion-exchange chromatography of the bacteria-free reaction mixture. Yield of isolated R-5-P was about 60% of the theoretical recovery.